How wars are won and lost vulnerability and military power - Gentry, John A. 1949- (Praeger Security International, 2012)
Military power is a key component of state power. Yet for all the attention statesmen, soldiers, and scholars give to military power, it remains a loose concept. A considerable academic effort has catalogued characteristics of great power wars. Scholars know much about individual wars, and they understand general patterns of war. But prominent theories of military power as a determinant of strategic political/military outcomes remain crude. The purpose of this book is to present, illustrate, and test an alternative general theory of military power defined as an ability to consistently, favorably influence strategic military outcomes -- that is, how and why actors win and lose wars. It also aims to use the theory to help explain why the United States has done very well in some of its military operations but very poorly in others.